2008
DOI: 10.1086/589869
|View full text |Cite
|
Sign up to set email alerts
|

Ritonavir‐Boosted Atazanavir, Methadone, and Ventricular Tachycardia: 2 Case Reports

Abstract: We describe 2 cases of symptomatic ventricular tachycardia associated with prolonged QT interval. Both patients were infected with the human immunodeficiency virus and were receiving treatment with ritonavir-boosted atazanavir and methadone. Discontinuation of atazanavir in both cases resulted in a reduction in the QT interval and cessation of arrhythmia. We concluded that atazanavir contributed to prolonged corrected QT interval and subsequent ventricular tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…ATV is known to produce QT prolongation and TdP in clinical use [8][9][10] . In this study, we demonstrated that ATV directly inhibits both the cellular hERG K + channel current and hERG K + channel protein trafficking at similar concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATV is known to produce QT prolongation and TdP in clinical use [8][9][10] . In this study, we demonstrated that ATV directly inhibits both the cellular hERG K + channel current and hERG K + channel protein trafficking at similar concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Santimaleeworagun et al reported that ATV induced first-degree atrioventricular block and ventricular tachycardia [10] . In addition, there has also been a report of QT interval prolongation or the risk of ventricular tachycardia (VT) with combined treatment using ATV and other drugs such as methadone [9] . Recently, it was reported that ATV did not prolong the QTc interval and did not increase QTc dispersion [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This adversity was not originally reported during the clinical development of the drug and has only rarely been noticed in the post-marketing period. 45 ATV has been shown to prolong the PR interval in electrocardiograms performed on healthy volunteers as well as in HIV-infected patients. Abnormalities in atrioventricular conduction are generally asymptomatic, concentration-dependent and limited to fi rst-degree atrioventricular block.…”
Section: Toxicitymentioning
confidence: 95%
“…259,261 One patient had taken an overdose of flunazepam prior to his episode, 259 while another was positive for cocaine per urine toxicology. 261 Two patients had their current ART discontinued, 259 while another was discharged with a plan to be tapered off of methadone. 261 In general, the benefits of therapy should be weighed against the potential for adverse effects, taking into consideration patient-specific risk factors and whether increased vigilance with respect to cardiac monitoring is warranted.…”
Section: Compounding Adverse Effectsmentioning
confidence: 99%